ATOR 2021: Summary and conclusions - Ulimwengu, John M.; Constas, Mark A.; Ubalijoro, Éliane; Collins, Julia (AKADEMIYA2063, 2021)
The 2021 Annual Trends and Outlook Report (ATOR) includes three major sections in addition to the chapter tracking progress toward Comprehensive Africa Agriculture Development Programme (CAADP) goals. First, the report assesses the impact of COVID-19 on African economies with a focus on food systems from access to inputs to household consumption. Second, it reviews interventions to stop the spread of the pandemic and contain its negative impact on food systems across the continent. Third, the report highlights innovations in measurement needed to better understand the effects of the pandemic and the factors contributing to resilience.